Word Association Norms : Grade School Through College - Palermo, David S. (Book collections on Project MUSE., 1964)
In an effort to stimulate research and to provide raw materials for a wide variety of behavior studies, the authors present a complete tabulation of the responses of 4,500 subjects, ranging from fourth grade through college age, to a word association test of 200 words. The norms thus obtained will be useful to psychologists, linguists, psychiatrists, anthropologists, and others studying verbal behavior and related questions. The data are arranged in three major tables: first, a tabke of the responses made to each stimulus word, including the frequency of each response in each sex-grade group.